THE IMPORTANCE OF THE FRUIT AND VEGETABLE SECTOR IN INCREASING THE COMPETITIVENESS OF AGRICULTURE AND THE FOOD INDUSTRY - Dr. Barno Raxmonova; Sardorbek Tojiddinov (Journals Park Publishing, 2024)
The article discusses ways to improve the efficiency of fruit vegetable production in Uzbekistan. As a result of the analyzes, the effectiveness of fruit vegetable products grown in the Andijan region was studied.
Keywords: fruit and vegetable production, economic efficiency, cost, profit, profitability.